A need for evidence-based clinical practice guidelines for the use of heparins in the elderly - Isabelle Gouin-Thibault (Dove Medical Press, 2010)
Isabelle Gouin-Thibault1,2, Virginie Siguret1,2, Eric Pautas2,31Assistance Publique Hôpitaux de Paris, Laboratoire d’Hématologie, Hôpital Charles Foix, Paris, France; 2Université Paris Descartes, INSERM U, Paris, France; 3Assistance Publique Hôpitaux de Paris, Unité de Gériatrie Aiguë, Hôpital Charles Foix, Paris, FranceAbstract: Low-molecular-weight heparins (LMWHs) have been widely studied in pivotal clinical trials or in several meta-analyses. However, the safety and optimal use of LMWHs in high-risk patients such as the very elderly remains uncertain since these patients are usually excluded from clinical trials. In terms of LMWHs in the elderly, the main concerns are renal failure and the risk of accumulation. A clinical approach consisting of a LMWH dose reduction in the elderly should be considered with great caution in terms of efficacy, since it has been tested neither in the treatment of VTE nor in VTE prophylaxis. If monitoring is considered in patients receiving therapeutic dose LMWHs, appropriate target ranges for peak anti-Xa activity levels should be used and so far, no anti-Xa activity-based guidelines have been issued. Moreover, no data support any laboratory monitoring in elderly patients treated with prophylactic dose LMWHs.Keywords: elderly patients, low-molecular-weight heparin, renal insufficiency, evidence-based medicine